MENINGKATKAN HASIL BELAJAR SISWA MATERI BAHASA INGGRIS MELALUI PEMBELAJARAN DENGAN PENGGUNAAN MEDIA AUDIO VISUAL SMPN 4 MATARAM - ANDI MASANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to determine the improvement of student learning outcomes in the class of SMPN 4 Mataram. This type of research is Classroom Action Research (CAR). Based on the results of the study, it can be concluded that the application of the use of audio-visual media can improve students' Inggrisn learning outcomes. Before applying the use of audio-visual media in the first cycle, the average value of the class in the cognitive domain was 67.3, the percentage of completeness was 58.33%. In the second cycle, the students' learning outcomes were the average class at 77.3 with a completeness percentage of 83.33%. In cycle III the learning outcomes of students are the average class in the cognitive domain of 87.5 with a 100% completeness percentage. Based on the results of the research and discussion, as well as the analysis of the data that has been described, it can be concluded that learning the use of audio-visual media can improve learning outcomes of Indonesian class VII SMPN 4 Mataram in the Even Semester of the 2019/2020 Academic Year. ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar peserta didik kelas SMPN 4 Mataram. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Berdasarkan hasil penelitian, dapat disimpulkan bahwa penerapan penggunaan media audio visual dapat meningkatkan hasil belajar Bahasa Inggris peserta didik. Sebelum diterapkan penggunaan media audio visual pada siklus I nilai rata -rata kelas pada ranah kognitif 67,3 persentase ketuntasan 58,33%. Pada siklus II hasil belajar peserta didik yaitu rata-rata kelas pada 77,3 dengan persentase ketuntasan 83,33%. Pada siklus III hasil belajar peserta didik yaitu rata-rata kelas pada ranah kognitif 87,5 dengan persentase ketuntasan 100%. Berdasarkan hasil penelitian dan pembahasan, serta analisis data yang telah diuraikan dapat disimpulkan bahwa pembelajaran penggunaan media audio visual dapat meningkatkan hasil belajar Bahasa Inggris kelas VII SMPN 4 Mataram pada Semester Genap Tahun Pelajaran 2019/2020.